TURISMO RURAL EM BATAGUASSU - MS: UM ESTUDO SOBRE SUA IMPORTÂNCIA E SEU DESENVOLVIMENTO LOCAL - Erika Lima Muss; Denise Bomtempo (Universidade do Oeste Paulista, 2007)
Nowadays, the Tourism is an important economic activity, in a global scale, especially in Brazil which has a great natural and cultural potential, not yet duly explored. In the city of Bataguassu - MS, there is a propitious environment for the development of tourist activities. The city is known for the River Paraná, which was transformed into an immense lagoon, with the Power Plant Sergio Motta. With the lagoon formation, it was transformed into an attractive place for the development of fishing. However, the outskirts of the lagoon were structuralized to for the tourists who were looking for a place to fish. The properties had been transformed into inns. This option, for organizing the property for the fisherrmen, was one of the alternatives adopted by the land proprietors to win the difficult times in familiar agriculture.